Improving the Activeness of Islamic Religious Education Learning Through the Problem Based Learning Model at SDN PalumbonSari III - Salma Gania; Syarifatul Ulfa; Ahmad Dhiyaauddin; Nur Aini Farida; M.Makbul (al-Afkar, Journal For Islamic Studies, 2025)
Problem-Based Learning (PBL) directs students to learn naturally by participating in solving problems. The PBL approach uses real-life problem situations to build problem-solving skills, critical thinking, and understanding of key concepts from the subject matter. The Classroom Action Research (PTK) method was used in this research to solve problems that arise in the learning process and to increase student participation in learning at SDN Palumbonsari III. PTK consists of two cycles, with four stages each: planning, implementation, observation, and reflection. To analyze the collected data, formulas corresponding to activity indicators are used. The research results show that the problem-based learning model improves student learning outcomes. The percentage value increased by 70% in cycle I and 100% in cycle II. Based on data analysis, it was concluded that this model can be used well in the learning process and can increase student participation in Islamic Religious Education lessons in class VI at SDN Palumbonsari III, East Karawang.